Upskilling Youth Entrepreneur Melalui Konversi Buah Maja Sebagai Produk Sanitasi Mudah Replikasi - Rosdaliani, Andi; Nursyam, Aisyah; Muhammad Irfan Taufan Asfar, Andi; Muhamad Iqbal Akbar Asfar, Andi; Nurannisa, Andi; Wulandari, Fani (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
Maja fruit in Pettungnge Hamlet, Maggenrang Village is a problem that must be solved immediately, where maja fruit has been left alone and even thrown into the river which can cause river water pollution. Whereas maja fruit is seen from its compounds which are very potential to be used as an easily replicable sanitation product in the form of hand washing soap such as, saponin compounds that can cause maja fruit to foam. The purpose of this service activity will provide solutions to partners of the Dropout Girls Group in processing maja fruit into easy replicable sanitation products in the form of hand washing soap and increase partner knowledge and skills. The implementation method is carried out in a society parcipatory manner which is carried out by doing, which consists of three main stages, namely the stages of counseling and socialization, training, and mentoring. The results obtained from this service activity show an increas in the knowledge and skills of partners in utilizing maja fruit into easy replicable sanitation products in the form of high economic value hand washing soap with an increase of 95% each. In addition, with this increase in partner skills, it can also build the entrepreneurial spirit of partners while realizing SDGs points 3 and 12, namely healthy and prosperous villages and environmentally conscious village consumption and production.